The Impacts of the use of Thematic & Chronologic Multi-modal Information Representation on Sequential and Global Students’ Historical Understanding - Ling Weay Ang; Sellappan Palaniappan (Journal of Informatics and Web Engineering)
This study examined the two different modes of multi-modes information presentations that affected sequential and global learners' history understanding: thematic and chronological. A total of 134 secondary schools’ students were enrolled (69 learning in chronological mode, 65 learning in thematic mode). Before the start of the treatment session, students were given a pre-test. The results showed that multimodal information presentation did not have a significantly great impact on historical learning or between pupils who learn in chronological and thematic ways. The chronological frame of reference technique, which reflected an interactive timeline, was reported to have supported students' sequential learning in chronological mode. Students who learned in thematic mode, on the other hand, had greater gains in points of historical understanding than students who learned in chronological mode. Students who exhibited a significant difference in their assessment of historical understanding proved the effectiveness of multimedia information presentation in acquiring history-related abstract ideas.